2007
DOI: 10.1161/strokeaha.106.479485
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Right-to-Left Shunt With Transcranial Doppler and Vertebrobasilar Recording

Abstract: Background and Purpose-Right-to-left shunt (RLS) due to patent foramen ovale is a well-established risk factor for cryptogenic stroke and is highly prevalent in cases of migraine, cluster headache, and obstructive apnea. It can be diagnosed by gaseous-contrast transcranial Doppler, yet in a small percentage of cases it cannot be done owing to an insufficient temporal window. The aim of the study was to compare transtemporal with transoccipital approaches for gaseous-contrast transcranial Doppler for RLS diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 26 publications
1
38
0
2
Order By: Relevance
“…The lower sensitivity of the VBC recording might depend on the lower amount of blood in the vertebrobasilar system (20% of the carotid circulation) [7] . A higher number of MB in the MCA than in VBC was also seen (number of MB at rest plus MB after VM = 16.1 8 13.4 vs. 10.6 8 7.2), according to previous observations [8] . A positive correlation between MB in the MCA and VBC was observed only for the medium and large shunts (k = 0.91, p !…”
supporting
confidence: 82%
“…The lower sensitivity of the VBC recording might depend on the lower amount of blood in the vertebrobasilar system (20% of the carotid circulation) [7] . A higher number of MB in the MCA than in VBC was also seen (number of MB at rest plus MB after VM = 16.1 8 13.4 vs. 10.6 8 7.2), according to previous observations [8] . A positive correlation between MB in the MCA and VBC was observed only for the medium and large shunts (k = 0.91, p !…”
supporting
confidence: 82%
“…The contrast medium was injected with a 21-gauge needle, possibly in the right antecubital vein. The contrast medium was a mixture of 9 ml of saline 0.9% mixed with 1 ml of air through two syringes (at least 10 passages) [15,16]. The velocity of injection was 2.5 ml/s [16].…”
Section: Methodsmentioning
confidence: 99%
“…A previous study confirmed the possibility and reliability of MES monitoring at the basilar artery using basilar artery TCD recording for the diagnosis of right-to-left shunts. 17 Our study is the first to our knowledge to demonstrate the use of MES monitoring in patients with posterior circulation ischemia. MES monitoring at the basilar artery could be an alternative method in other research studying posterior circulation emboli, especially for subjects with an insufficient temporal acoustic window.…”
Section: Discussionmentioning
confidence: 71%